Entrepreneurship Education and Its Impact on Microenterprise Growth: Evidence from Rural Areas in South Sulawesi - Jessica Felicia (Generasi Sains Indonesia, 2025)
Entrepreneur education has been widely advanced as a tool in generating growth of microenterprises; however, its applicability in rural environment is controversial. The current research problem is the influence of entrepreneurship education on the performance of microenterprise in the rural South Sulawesi region, Indonesia. Using a mixed-method, the study incorporated survey data in the form of a mixed research study with focus group discussions to assess the transformation of business practices, sales performance, and market expansion. The results show that entrepreneurship education positively determines the financial management, digital marketing adoption, and customer engagement, which create quantifiable improvements in sales and effective operations. On the other hand, the impacts on employment creation and product diversification seem to be less significant, which indicates that education by itself cannot completely address structural limitations including insufficient access to finance, poor infrastructure, and digital differences. The findings highlight the significance of situating training material and aligning education with development policies in general. The paper finds that entrepreneurship education may act as a driving force in the development of microenterprises, but its effectiveness depends on the presence of favorable ecosystems and program models that address the unique needs of rural entrepreneurs.